2009
DOI: 10.1177/0011128709336942
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Police Strength in Large U.S. Cities During the 1990s

Abstract: The 1990s represented a unique decade in which to analyze the determinants of police strength in the United States. This decade was a time in which crime initially increased, then substantially decreased. Furthermore, this decade also was characterized by increases in the minority population throughout large American cities. Finally, the 1990s were characterized by increasing police budgets. These realities have direct implications for the competing theories of police growth. This research examines the determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 48 publications
4
36
1
Order By: Relevance
“…Results from cross-sectional studies typically show that the percentage of the overall visible minority population does not exert as much influence on police strength as the size of the black (Eitle et al 2002;Holmes et al 2008;Ruddell et al 2011;Sever 2001) or Latino populations (Holmes et al 2008;Jackson 1985). Zhao et al (2012) and McCarty, Ren, and Zhao (2012), however, found positive relationships using the overall visible populations and police deployment. Like other indicators of police strength, these results may be dependent upon the jurisdictions and eras examined.…”
Section: Minority Threatmentioning
confidence: 89%
“…Results from cross-sectional studies typically show that the percentage of the overall visible minority population does not exert as much influence on police strength as the size of the black (Eitle et al 2002;Holmes et al 2008;Ruddell et al 2011;Sever 2001) or Latino populations (Holmes et al 2008;Jackson 1985). Zhao et al (2012) and McCarty, Ren, and Zhao (2012), however, found positive relationships using the overall visible populations and police deployment. Like other indicators of police strength, these results may be dependent upon the jurisdictions and eras examined.…”
Section: Minority Threatmentioning
confidence: 89%
“…It stands to reason that the size of metropolitan police departments is, at least in part, a function of a jurisdiction's ability to pay for such a service. Many recent studies on police strength have supported this expectation (Holmes et al, 2008;McCarty et al, 2012;Zhao et al, 2012). A number of scholars have suggested that a city's tax base is the best indication of available funds for law enforcement Kent & Jacobs, 2005).…”
Section: Alternative Accounts and Other Controlsmentioning
confidence: 97%
“…The associated costs of operating a municipal government are high and, like all public budgets, there are limited financial resources (Nunn, 2001). A large portion of the budget for many cities, particularly those serving large urban areas, is set aside for law enforcement functions (see, e.g., Donahue & Miller, 2005;Gerber & Hopkins, 2011;McCarty, Ren, & Zhao, 2012). Skogan (1976) recognized as much when he found that big-city police organizations expend considerable resources trying to find a proper equilibrium between efficiency and effectiveness.…”
Section: Introductionmentioning
confidence: 99%